A case-control study of bleeding risk in children with 22q11.2 deletion syndrome undergoing cardiac surgery - T. Blaine Crowley; Ian Campbell; Abinaya Arulselvan; David Friedman; Elaine H. Zackai; Tracy R. Geoffrion; Char Witmer; J. William Gaynor; Donna M. McDonald-McGinn; Michele P. Lambert (Platelets)
Previous research suggests that individuals with 22q11.2 deletion syndrome (DS) have an increased risk of bleeding following cardiac surgery. However, current guidelines for management of patients with 22q11.2DS do not provide specific recommendations for perioperative management. This study sought to identify specific risk factors for bleeding in this patient population. Examine the factors determining bleeding and transfusion requirements in patients with 22q11.2DS undergoing cardiac surgery. This was a single center review of patients who underwent cardiac surgery at the Children’s Hospital of Philadelphia from 2000 to 2016. Data was extracted from the medical record. Frequency of bleeding events, laboratory values, and transfusion requirements were compared. We included 226 patients with 22q11.2DS and 506 controls. Bleeding events were identified in 13 patients with 22q11.2DS (5.8%) and 27 controls (5.3%). Platelet counts were lower among patients with 22q11.2DS than in control patients, but not statistically different comparing bleeding to not bleeding. Patients with 22q11.2DS received more transfusions (regardless of bleeding status). However, multivariate analysis showed only procedure type was associated with increased risk of bleeding (p = .012). The overall risk of bleeding when undergoing cardiac surgery is not different in patients with 22q11.2DS compared to non-deleted patients. Though platelet counts were lower in patients with 22q11.2DS, only procedure type was significantly associated with an increased risk of bleeding.